Simulation of Moving Obstacle Avoidance for Auto Guided Land Vehicle - Altaei, Mohammed Sahib Mahdi; Al-Ani, Laith A; Khamis, Qudama (Al-Nahrain Journal of Science, 2018)
This paper concerned with simulating the behavior of designed control system that tries to govern robot to safely passing a path containing moving obstacle ahead. The used robot carried some specific sensors are used to sense the existence of obstacles along the moving path, these sensors are IR sensor that used to detect the obstacle and visual sensor that used to measure the size and the distance for the obstacle. In order to overcome the obstacle, the controller assumes new transient away point at the far side of the obstacle, and guides the robot to pass through that point. The position of such transient point is depending on the size and direction of the obstacle. Then, whenever the robot close to the transient point, the controller guides the robot to identify the intended path again. This algorithm enables the robot to move far away from the moving obstacle and then back it into planned path.